2006
DOI: 10.1097/01.aog.0000227787.24587.d1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Behavior of Stage II-IV Low-Grade Serous Carcinoma of the Ovary

Abstract: Metastatic low-grade serous carcinoma of the ovary is characterized by young age at diagnosis and prolonged overall survival. Segregating women with this diagnosis in future clinical trials is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
207
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 257 publications
(222 citation statements)
references
References 34 publications
12
207
2
1
Order By: Relevance
“…Overall survival rates for the two types differ dramatically, with median survival being 82 months [4] versus 30 months [5] for Types I and II, respectively. This difference is despite the initial sensitivity of type II tumours to standard carboplatin and paclitaxel chemotherapy.…”
Section: Classification Of Eocmentioning
confidence: 97%
“…Overall survival rates for the two types differ dramatically, with median survival being 82 months [4] versus 30 months [5] for Types I and II, respectively. This difference is despite the initial sensitivity of type II tumours to standard carboplatin and paclitaxel chemotherapy.…”
Section: Classification Of Eocmentioning
confidence: 97%
“…The MD Andersen Cancer Centre group went on to describe the clinical features of low-grade serous carcinomas, which include: presenting in younger patients, frequently in high-stage, and showing lower responses to chemotherapy compared with high-grade serous carcinomas. 11 Subsequent studies confirmed that only occasional low-grade serous carcinomas exhibit complete response to standard chemotherapy in the neoadjuvant or recurrent setting. [12][13][14][15] With the increasing evidence suggesting that neoadjuvant chemotherapy is an equivalent or superior treatment regimen for advanced stage ovarian cancer, the selection of cases of patients who are most likely to respond remains a foremost clinical problem, which begins with accurate diagnosis.…”
mentioning
confidence: 93%
“…Most patients diagnosed with OC, survival is theorized to be 100%, who are still alive after 5-years, are presumably living with the disease rather than living disease-free. 5 Our analysis demonstrated that the DFS was 18.3 months (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The Surveillance, Epidemiology and End Results-SEER database from 1995 to 2007 with epithelial OC who were actively followed-up and age 20 years or older were included for analyzing OS in the United States (40.692 patients) and OS was 65%, 44%, and 36% at 2, 5, and 10 years, respectively.…”
Section: Discussionmentioning
confidence: 86%
“…Older age at diagnosis was often associated with comorbidities and functional deficits that impact their survival. Gershenson et al 27 reported on a cohort of 112 patients with stage II-IV low-grade serous carcinoma from M.D. Anderson Cancer Center in 2006, and noted age older than 45 years at diagnosis was associated with longer survival.…”
Section: Discussionmentioning
confidence: 99%